FACTORS THAT ENCOURAGE SMALL AND MEDIUM MICRO ENTERPRISES TO LOAN IN SHARIA BANKING - Alfian Tri Kusuma; Amir Hidayatulloh (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2020)
The purpose of this study was to analyze the influence of knowledge, motivation, reference groups, and location of banks on the interest of micro, small, and medium enterprises (MSMEs) to lend funds to Islamic Bank. The population in this study is MSMEs in the unique region of Yogyakarta. This study's sample is the MSMEs in the unique region of Yogyakarta who is customers of Islamic Bank. The sampling techniques in this study use convenience sampling. Data collection techniques in this study were carried out by distributing questionnaires and obtained 50 respondents. The data analysis techniques of this study used multiple linear regression analyses with the help of SPSS tools. This study found that of interest of MSMEs to lend fund in Islamic Bank was influenced by knowledge, motivation, reference group, and the location of the bank